Hungarian Monitoring, 27 March 1990 . [Magyar rádiófigyelő], 1990. március 27 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Telephone interview with Polish government deputy spokesman - Gorbachev's personal cabinet holds its first meeting - The two large East German parties work on division of government posts - Romanian premier holds simultaneous talks in Cluj with Democratic Alliance of Hungarians in Romania (RMDSZ) and Vatra Românească representatives Domestic Affairs: - Evaluation of the elections, preliminary final results announced - Hungarian Democratic Forum (MDF) press conference - Gyula Horn holds press conference - János Kis talks to French newspaper about the border issue - Malév Hungarian Airlines halts its Beirut flights - Situation improves in Targu Mures - Threat on journalist Alajos Chrudinák's life Külpolitika: - Telefoninterjú a lengyel kormány helyettes szóvivőjével - Megtartotta első ülését Gorbacsov személyes kabinetje - Az NDK-beli két nagy párt már a kormányposztok szétosztásán dolgozik - Egyszerre tárgyaltak Kolozsváron az RMDSZ és a Vatra Romanesca képviselői Roman miniszterelnökkel Belpolitika: - A választások kiértékelése , megszületett a választás előzetes végeredménye - MDF sajtótájékoztató - Horn Gyula sajtótájékoztatója - Kis János nyilatkozata egy francia lapnak a határkérdésről - Leállította bejrúti járatait a MALÉV - A marosvásárhelyi helyzet javulásáról - Chrudinák életveszélyes fenyegetést kapott